How Does Social Capital Help Achieve High-Quality Education? - Yosi Arianti; Ridhah Taqwa (Labor Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
The purpose of this study is to examine how social capital is used to achieve high-quality education at SMAN Sumatra Selatan. This was a descriptive qualitative study with data collected through participant observation. The researcher was involved directly as well as witnessing the research process and conducting in-depth interviews with ten informants. The Miles and Huberman's were applied in the data analysis. The study's findings revealed the presence of social capital in SMAN Sumatra Selatan in the form of trust, networks, and social norms. Cooperation between the Government of the Province of South Sumatra and the Putera Sampoerna Foundation, as well as cooperation with companies, shown trust. The social network formed as a result of the partnership between SMAN Sumatra Selatan and the mass media, as well as education supporting companies. The social norms in the school were represented by four exceptional programs: academic programs, lifetime learning programs, the pathway to leadership programs, and boarding education programs. This school's social capital components included communicating with one another, working together, influencing one another, and being related to one another. They resulted in a structure of social relations that culminated in a high-quality school.